E-COMMERCE USAHA KECIL DAN MENENGAH KOTA PALEMBANG - Meileni, Hetty; Apriyanti, Desi; Pratiwi, Cindy Indah (Ekonomi & Bisnis, 2020)
The purpose of writing this report is to solve the problem in the city of Palembang, about the sales container of small and medium enterprises (UKM) that do not exist. The solution of the problem is Palembang city requires a system of information on the sale of UKM to support the improvement of the sales system in the Industry ERA 4.0. The benefits of this information system is to facilitate the seller in selling the product through UKM E-Commerce, and this information system can also facilitate the buyer in purchasing UKM products in the city of Palembang without having to come to the store or come to the sales stand. Data is collected based on direct observation of activities related to informatics learning. The result is the information system of small and medium enterprises (UKM) in Palembang city. The conclusion is that the small and medium business information system (UKM) uses PHP and MySQL programming language that can be accessed by the Admin, UKM product vendor, and buyer through a browser that can increase sales and become a container of UKM in Palembang